MULTICULTURAL LEARNING THROUGH CALLIGRAPHY ART CLASSES AT THE PIJI WETAN CULTURAL VILLAGE - Gita, Randi; Hartono, Hartono; Vania, Febianti (Arty: Jurnal Seni Rupa, 2025)
This study aims to analyze multicultural learning through calligraphy art in Piji Wetan Cultural Village, Kudus, Central Java, and examine its influence on local cultural identity. The approach used is qualitative with a case study method, where data is collected through observation, in-depth interviews, and documentation. The results of the study indicate that the process of learning calligraphy art in Piji Wetan Cultural Village is carried out inclusively and involves various levels of society, from children to adults. This learning does not only focus on Arabic calligraphy writing techniques, but also integrates religious values and local art elements. The resulting works reflect a harmonious blend of Islamic calligraphy art with traditional Kudus decorative patterns and motifs. These works demonstrate the innovation of students in combining local motifs with calligraphy art without eliminating the authenticity of the writing character. Calligraphy art in Piji Wetan Cultural Village plays an important role in preserving local cultural identity through cross-cultural teaching, which not only enriches calligraphy art aesthetically, but also strengthens understanding and appreciation of culture and religion. The influence of learning calligraphy art is seen in the formation of a stronger local cultural identity, increased creativity of the younger generation, and pride in local artwork. In conclusion, the art of calligraphy in Piji Wetan Cultural Village has succeeded in becoming an affective multicultural learning medium, which not only emphasizes the artistic aspek but also strengthens the community’s relationship with their cultural heritage.